Urban design guidance urban design frameworks, development briefs and master plans - Cowan, Robert, 1950- (Thomas Telford, 2002)
The aim of this guide is to explain what design guidance is, how it should be prepared, what clients expect, what services consultants offer, and what resources are required. The book is addressed to anyone involved in commissioning, preparing or using design guidance.
At foot of title: Urban Design Alliance and Urban Design Group.
Keywords: City planning -- Great Britain.; elektronické knihy; electronic books